Syphilis infection among homosexual men reporting contact with syphilis: a case control study. Issue 4 (19th August 2012) - Weerakoon, Ajith P; Fairley, Christopher K; Read, Tim RH; Bradshaw, Catriona; Forrester, Catherine; Bissessor, Melanie; Denham, Ian; Chen, Marcus Y
Abstract : Objective: High rates of syphilis have been reported among men who have sex with men (MSM) internationally. Guidelines recommend presumptive treatment of sexual contacts of individuals with syphilis at the point of care. The aim of this study was to determine the proportion who were infected with syphilis and the factors predictive of infection among men reporting contact with a man with syphilis. Design: Contacts who were syphilis infected (cases) were compared with those who were uninfected (controls). Setting: This study was conducted at the main public sexually transmitted diseases clinic in Victoria, Australia. Participants: One hundred and seventy-two MSM presenting as sexual contacts of men with syphilis at a sexual health service in Melbourne, Australia, between July 2007 and October 2011 were assessed for syphilis. Outcome measures: Proportion of MSM who are infected with syphilis and factors associated with infection. Results: Of the 172 men who presented reporting contact with syphilis, 26 (15%, 95% CI 10 to 20%) had syphilis. One man had primary syphilis, 4 had secondary syphilis, while the remaining 21 had early latent syphilis. Infection was associated with unprotected anal sex over the prior 3 months (adjusted OR 6.1, 95% CI 1.4 to 26.8). Conclusions: One in seven men presenting as contacts of syphilis had syphilis infection, most of whom were latently infected. Contacts reporting recent unprotected anal sex were more likely to have syphilis.